2017
DOI: 10.1021/acs.jced.7b00485
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Vapor–Liquid Equilibrium Data for the Hexafluoroethane (R116) + n-Butane System at Temperatures from 273 to 323 K

Abstract: Isothermal vapor−liquid equilibrium (VLE) data for the system of hexafluoroethane (R-116) + n-butane are reported in this paper. The measurements were undertaken at six different temperatures ranging from 273.27 to 323.19 K, with pressure ranging from 0.104 to 3.742 MPa. Two of the temperature sets were measured below, and the remaining four were measured above, the critical temperature of R116. The measurements were performed in a "static-analytic" type VLE apparatus. The sampling of the equilibrium phases wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…System pressure as a function of the number of carbon atoms in the n -alkane molecule for systems of R-116 + (C 3 to C 10 ) n -alkanes at a R-116 molar composition ( x 1 ) of 0.1 and at temperatures of between T = (292.94 and 296.24) K. Data were sourced from this work as well as the works of Ramjugernath et al ,, and Williams-Wynn et al , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…System pressure as a function of the number of carbon atoms in the n -alkane molecule for systems of R-116 + (C 3 to C 10 ) n -alkanes at a R-116 molar composition ( x 1 ) of 0.1 and at temperatures of between T = (292.94 and 296.24) K. Data were sourced from this work as well as the works of Ramjugernath et al ,, and Williams-Wynn et al , …”
Section: Resultsmentioning
confidence: 99%
“…However, the discrepancies between the data and the models were high with AARD values between 5.5 and 7.2%. Despite the fit of the models not being as accurate as in the case of other systems involving hexafluoroethane and an alkane, ,,,, the PR MC + WS/NRTL model was used here to ensure that parameters for this model were available for all of the measured systems in the homologous series of R-116 + n -alkanes. The parameters that are presented in Table are also plotted in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been little reported in the open literature on studies related to the use of fluorinated refrigerants as solvents for hydrocarbon systems. A partial list of authors who have reported the vapor–liquid equilibrium (VLE) data of hexafluoroethane (R-116) with n -alkanes was supplied by Ramjugernath et al Authors who have reported VLE measurements of hexafluoroethane and alkanes include Ramjugernath et al , and Zhang et al. , The system of R-116 and ethane was investigated by Zhang et al, whereas VLE data sets for the system of R-116 with both propane and n -butane were investigated by Ramjugernath et al…”
Section: Introductionmentioning
confidence: 99%
“…[8]. For the R-23 + n-hexane system, the data of Williams-Wynn et al [4] were used, and for the R-116 + n-hexane, the data that were reported by Ramjugernath et al [9] were extrapolated to the critical point.…”
Section: Introductionmentioning
confidence: 99%